HUBUNGAN TINGKAT PENGETAHUAN BENCANA DENGAN KESIAPAN MANAJEMEN BENCANA PADA PERAWAT PSC 119 GIANYAR - I Made Dwie Pradnya Susila (STIKES ADVAITA MEDIKA TABANAN, 2019)
ABSTRACT Nurses who work at the Public Safety Center (PSC) 119 need to have knowledge and disaster management readiness.. Knowledge is the main factor and is the key to preparedness. Preparedness is one part of the disaster management process and in the concept of disaster that is developing now, the importance of preparedness is one of the important elements of prevention activities that are pro-active in disaster risk reduction, prior to the occurrence of a disaster. The purpose of this study was to find out the relationship between the level of disaster knowledge and disaster management readiness nurses in Gianyar PSC 119. This study uses a correlation research design, with a total sample of 39 people. Sampling technique by non probability sampling, namely total sampling. The instrument for collecting data is using a knowledge questionnaire about disasters and disaster management readiness. Data were analyzed using the Spearman Rho test. The level of knowledge about disasters in nurses was mostly categorized as sufficient, namely as many as 20 respondents (51.3%). The readiness of disaster management in nurses was mostly categorized as moderate, namely as many as 20 respondents (51.3%). The results of the Spearman Rho test obtained a value of p = 0.001 and a value of r = 0.528, so it can be concluded that there was a relationship between the level of disaster knowledge and disaster management readiness nurses in Gianyar PSC 119, with a medium correlation strength. It is recommended to nurses to increase disaster management knowledge and readiness.